Rental and sale prices of agricultural lands under spatial competition - Marten Graubner; Silke Hüttel (Letters in Spatial and Resource Sciences, 2024)
Much of the land economics literature has largely ignored the spatial nature of competition and related differences between farmland rental and sales markets when assessing return rates from farming, the capitalization of agricultural, environmental and energy policy into land values, and climate change impacts. We propose a model for price formation in both markets under a spatial competition framework. We demonstrate that price formation differs, particularly under policy-induced output price shocks.We suggest that using the rent-price ratio as an approximation for expectations in the net returns of farming, based on the net present value model, may produce biased results. In consequence, studies relying on land prices need to control for local land competition, farming structure, and policies.
Keywords: L13; Q12; Q18; 330; Land markets; Rent-price Ratio; Spatial competition; Policy capitalization; Price formation